The importance of Monitoring and Evaluation of the Application of Indonesian Language in SPK School: A Case Study of Public Policies Implementation on national language use in Education - Zahran, Wahidin Septa (Technium Social Sciences Journal, 2022)
One thing that is trending in the world of education today is an international standard school or what is currently known as the Cooperation Education Unit (SPK). The advantages of this school in addition to using national and international curricula, also use English as the language of instruction. The latter then creates a new problem, considering that many children who attend SPK schools cannot speak Indonesian language, even though this is the national language of Indonesia. This research is aimed at answering the questions of how to implement the use of Indonesian language in the SPK schools, how monitoring and evaluation are carried out and what efforts must be made so that Indonesian children who study in SPK Schools can communicate in Bahasa Indonesia well and keep having the character and identity as Indonesian. This is a qualitative research with a case study approach. Data collection used semi-structured interviews with 11 people consisting of 1 SPK principal and 10 parents of students. The results of this study indicate that the monitoring and evaluation method for supervising the use of Indonesian language which consists of documentation, surveys, observations, and FGDs, needs to be more intensively carried out in SPK schools so that the goal to produce students who do not only excel academically but also understand and possess the character and identity as Indonesian.